2009
DOI: 10.1055/s-0029-1240627
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Natural Compounds Isolated from the Seeds ofGarcinia afzelii

Abstract: The new compounds guttiferone O ( 1) and 3-methoxycheffouxanthone ( 2) have been isolated from the seeds of Garcinia afzelii Engl., together with nine known compounds: 2-hydroxy-1,7-dimethoxyxanthone ( 3), smeathxanthone A ( 4), 1,5-dihydroxyxanthone ( 5), 1,6-dihydroxy-5-methoxyxanthone ( 6), cheffouxanthone ( 7), 1,3,5-trihydroxyxanthone ( 8), smeathxanthone B ( 9), isoxanthochymol ( 10) and guttiferone E ( 11). Their structures were elucidated by means of 1D and 2D-NMR techniques. All the isolates showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Of the isolated compounds, only Garcinone inhibited both p50 and p65 activation. In addition, guttiferone O and 3-methoxycheffouxanthone compounds of Garcinia afzelli seeds inhibited the proliferation of cancer cells in a dose dependent fashion (Lannang et al 2010).…”
Section: Xanthones and Their Derivativesmentioning
confidence: 95%
“…Of the isolated compounds, only Garcinone inhibited both p50 and p65 activation. In addition, guttiferone O and 3-methoxycheffouxanthone compounds of Garcinia afzelli seeds inhibited the proliferation of cancer cells in a dose dependent fashion (Lannang et al 2010).…”
Section: Xanthones and Their Derivativesmentioning
confidence: 95%
“…Our literature review found no previous studies involving the evaluation of the genotoxic potential of the Garcinia or Rheedia extracts. Nevertheless, several species of this genus showed the presence of benzophenones, xanthones and bioflavonoids as main constituents (Deachathai et al, 2006;Lannang et al, 2010;Panthong et al, 2006), and, for some of these compounds, there are genotoxic and antigenotoxic studies. Almanza et al (2011) reported that the benzophenone acuminophenone A, and the xanthones formoxanthone C and macluraxanthone isolated from Rheedia acuminate showed no mutagenicity on several Salmonella typhimurium strains, but on the other hand, these compounds promoted a strong reduction of mutagenic effect induced by hydrogen peroxide.…”
Section: Compoundmentioning
confidence: 99%
“…The same compound tested in vitro exhibited antiviral activity on HIV-1-infected MT-4 cells and MDCK cells infected with influenza virus. 34 Trihydroxyxanthones have also been shown to be monoamine oxidase 25,26 and Na/K-ATPase inhibitors. 32 Finally, 1,3,7-trihydroxyxanthone also shows anticancer activity 33 and possesses monoamine oxidase, 25,26 α-glucosidase 27,28 and fatty acid synthase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%